Consumer Protection Law In Electronic Transactions: Between Rights And Obligations In The Digital Era - Widia, Windi Pangestu; Sakmaf, Marius S.; Jumiran; Husain (Mawaddah: Jurnal Hukum Keluarga Islam, 2024)
The digital age has given birth to electronic transactions (e-commerce) that offer convenience, speed, and broad access. However, it also opens up potential risks for consumers, such as fraud, data theft, and other violations of consumer rights. This research analyses laws and regulations, government regulations, legal theories, and expert opinions to discuss efforts to improve the effectiveness of consumer legal protection in electronic transactions. This research reveals findings related to consumer protection in electronic transactions contained in Law Number 8 Year 1999 on Consumer Protection and other laws and regulations. Consumers have the right to obtain information that is not misrepresented and covers all aspects, choose the product or service they want, get a fair price, guarantee the quality of the product or service, compensation for losses, and protection of personal data. Efforts to improve the effectiveness of consumer legal protection in electronic transactions require continuous updating and refinement of regulations, improving consumer digital literacy, socialising applicable regulations, increasing the capacity of law enforcement officials, facilitating consumer access to report violations, implementing more specific regulations for e-commerce, building an effective complaint system, and utilising technology for supervision and educationtechnology for monitoring and education.